Polymorphisms in Manganese Transporters SLC30A10 and SLC39A8 Are Associated With Children's Neurodevelopment by Influencing Manganese Homeostasis - Wahlberg, Karin E.; Guazzetti, Stefano; Pineda, Daniela; Larsson, Susanna C.; Fedrighi, Chiara; Cagna, Giuseppa; Zoni, Silvia; Placidi, Donatella; Wright, Robert O.; Smith, Donald R.; Lucchini, Roberto G.; Broberg, Karin (Frontiers in Genetics, 2018)
Background: Manganese (Mn) is an essential element but at excessive levels, it is neurotoxic. Even a moderate increase in Mn has been suggested to interfere with neurodevelopment in children. Genetics influencing Mn concentrations and toxicity is unclear. Objective: We assessed, in a cross-sectional study, whether common single-nucleotide polymorphisms in the Mn transporters SLC39A8 (influx) and SLC30A10 (efflux) are associated with neurodevelopment of children. Design: We genotyped SLC39A8 (rs13107325 C/T) and SLC30A10 (rs1776029 G/A and rs12064812 T/C) in Italian children (n=686, ages 11–14). We then used linear regression models to analyze associations between genotype, blood Mn concentrations, and neurodevelopmental outcomes including intelligence, behavior, motor function, and sway. Inferred causal relationships were evaluated using instrumental variables (IV) analysis. Results: For SLC30A10 rs1776029, the minor allele (A) was associated with increased average blood Mn of 41% (p<0.001), whereas minor alleles for rs12064812 (C) and rs13107325 (T) were associated with reduced blood Mn of 7% (p=0.002) and 15% (p<0.001) respectively. For children carrying genotypes associated with high blood Mn, we observed lower performance for certain IQ subtests, increased sway, and increased scores for behavioral problems. High Mn genotypes showed odds ratios of 2-4 (p≤0.01) for high scores in tests assessing ADHD-related behavior. IV analyses suggested that several of the associations were mediated by blood Mn. Conclusions: Our results suggest that common polymorphisms in SLC39A8 and SLC30A10 influence neurodevelopmental outcomes in children via differences in Mn homeostasis.